1784. Impact of a Novel Multidisciplinary Anti-Tubercular Stewardship Program in a Tertiary Care Center in India. (26th November 2018) - Singh, Sanjeev; Menon, Vidya; Pp, Binny; Dutt, Ananya; Kumar, Akhilesh; Et, Fabia; Kaye, Keith; Patel, Payal
Abstract: Background: Inaccurate diagnosis of tuberculosis (TB) and inappropriate anti- tubercular therapy (ATT) contribute majorly to the emergence of drug-resistant TB in India, particularly in the private healthcare sector. Our study evaluated the appropriateness of ATT as per Revised National TB control Program at our institution, a large private tertiary center in Kerala, India, after establishment of an Anti-Tubercular Stewardship program (ATTSP). Methods: The ATTSP was implemented as part of a recently developed Antimicrobial Stewardship Program (ASP). A multidisciplinary team including an administrative physician champion, pulmonologist, infectious disease specialist, and clinical pharmacists met twice weekly to review all patients initiated on ATT and to assess each case for appropriateness in terms of right indication, right drug, right dose, right frequency, and right duration. For each patient who had an inappropriate ATT prescription, appropriate recommendations based on standard treatment guidelines were filed in the charts and communicated to the primary team via email and phone. Compliance to recommendations was monitored. The clinical pharmacists followed up patients after discharge Results: Eight (52%) patients were prescribed ATT appropriately among the 153 patients reviewed from July 2017 to April 2018. Ninety-six interventions were recommended for the 73 cases with inappropriate ATT. Of these inappropriate ATT, 16 were for wrong indication, 27 for wrong drug, 52 for wrong dose and 1 for wrong frequency. Among the 137 accurately diagnosed cases of TB, 52% (71) were definite cases of TB while the rest were presumptive. Pulmonary, extra pulmonary and disseminated TB cases accounted for 45% (62), 50% (69) and 4% (6), respectively. ATT was appropriate in 63% (39) of pulmonary TB, and 54% (37) of extra pulmonary TB. Among 23 pulmonary TB patients with inappropriate ATT, 48% (11) were for wrong drug, 78%(8) for wrong dose and 17%(4) for wrong frequency. The 32 inappropriate extra-pulmonary TB cases included 19% (6) for inappropriate drug selection and 81% (26) for inappropriate dose. Compliance to ATTSP recommendations was 34%. Conclusion: TB in India is a vital target for ATT stewardship (10% of patients in this cohort had an inaccurate diagnosis of TB). ATTSP may be a worth initial target for novel ASPs in India. Disclosures: K. Kaye, Zavante Therapeutics, Inc.: Scientific Advisor, Consulting fee.